A Multidisciplinary Approach to the Diagnosis and Management of Obstructive Sleep Apnea: Current Strategies and Future Directions - Takhsinovna, Nasretdinova Makhzuna; Saydullo o'g'li, Bo'riyev Shaxzod (Journal of Science in Medicine and Life, 2025)
Obstructive Sleep Apnea (OSA) is a prevalent and underdiagnosed sleep disorder with significant public health implications, affecting nearly 1 billion people globally. Characterized by repeated episodes of upper airway obstruction during sleep, OSA is associated with excessive daytime sleepiness, cardiovascular morbidity, metabolic dysfunction, and impaired quality of life. Despite its high prevalence, a significant proportion of individuals with OSA remain undiagnosed and untreated. This article explores the current state of multidisciplinary approaches to the diagnosis and management of OSA. Emphasis is placed on the integration of otolaryngology, pulmonology, neurology, dentistry, sleep medicine, and behavioral health to achieve individualized and effective care. Recent advances in diagnostic technologies, therapeutic options including CPAP, oral appliance therapy, surgical interventions, and emerging future directions such as neurostimulation and precision medicine are discussed. The goal is to provide a comprehensive, evidence-based framework to improve clinical outcomes and enhance patient adherence.